Debt-equity choices, R&D investment and market timing - Lewis, Craig M; Tan, Yongxian (2016)
In this paper, we examine whether managers time their debt-equity choices to exploit market mispricing. Controlling for the level of external financing and corporate investment activities, we find evidence consistent with the market timing hypothesis. We find managers issue more equity relative to debt when analysts are relatively optimistic about firms’ long-term growth prospects. Moreover, equity issuers earn lower returns than debt issuers at subsequent earnings announcements. Controlling for research and development (R&D) investment, we find that, consistent with the market timing hypothesis and inconsistent with the extant empirical literature, the debt-equity composition of external financing predicts year-ahead stock return.